1996
DOI: 10.34080/os.v6.22993
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends of the Black-headed Gull Larus ridibundus population in Latvia

Abstract: The Black-headed Gull population in Latvia increased from 10,000 pairs in the early 1940s to 110,000 pairs in 1986, then decreased to about 40,000 pairs in 1994 and continues declining. The population changes have been more pronounced at coastal sites than at inland ones. Simultaneous changes in breeding success (a significant decline of average number of fledglings/pair since 1974), diet and feeding flights have taken place. Changes in the availability of anthropogenic food, appearance of new predators (mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…I motsats hartill finns det lampliga hackningslokaler langs stOrre delen av den gotlandska kusten. (A yen om skrattmasar i Lettland, vid de fOdomassigt speciella fOrhallanden som ratt dar, konstaterats proviantera upp till 70 km fran hackningslokalen (Viksne & Janaus 1986, Viksne m.fl. 1996 ar provianteringsturerna normalt mycket kortare, under 15 km och oftast ocksa under 10 km (Brandl & Gorke 1988),) I atskilliga av de i denna uppsats citerade arbetena har forsamrad hackningsbiotop, framfor allt i form av igenvaxning, frarnforts som en fOrklaring (eller bidragande forklaring) till skrattmasens minskning.…”
Section: Vad Har Orsakat Den Dokulnenterade Minskningen?unclassified
“…I motsats hartill finns det lampliga hackningslokaler langs stOrre delen av den gotlandska kusten. (A yen om skrattmasar i Lettland, vid de fOdomassigt speciella fOrhallanden som ratt dar, konstaterats proviantera upp till 70 km fran hackningslokalen (Viksne & Janaus 1986, Viksne m.fl. 1996 ar provianteringsturerna normalt mycket kortare, under 15 km och oftast ocksa under 10 km (Brandl & Gorke 1988),) I atskilliga av de i denna uppsats citerade arbetena har forsamrad hackningsbiotop, framfor allt i form av igenvaxning, frarnforts som en fOrklaring (eller bidragande forklaring) till skrattmasens minskning.…”
Section: Vad Har Orsakat Den Dokulnenterade Minskningen?unclassified
“…Black-headed gulls are long-lived birds, with an adult annual survival rate of 0.90 12 and a maximum recorded age of 33 years 13 . Their reproductive output is usually about 1.0–1.5 fledglings per breeding pair 14 , making adult survival one of the major components of population dynamics 15 . Black-headed gulls from breeding colonies in Poland winter in Western and Southern Europe 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason for the Coot decline is the expansion and predation of the introduced American Mink (Neovison vison; Brzeziñski & Marzec 2003). Some authors have not found conclusive evidence for waterfowl populations being limited by Mink predation (Arnold & Fritzell 1987, Halliwell & Macdonald 1996, Bartoszewicz & Zalewski 2003, but others have (Viksne et al 1996, Craik 1997, Ferreras & Macdonald 1999, Nordström et al 2003. Birds are exposed to Mink predation mostly during the breeding season (Gerell 1967), and some groups, such as Rallidae, seem to be particularly vulnerable (Day & Linn 1972, Chanin 1981, Ferreras & Macdonald 1999.…”
Section: Introductionmentioning
confidence: 99%